The Effect of Motivation and Work Discipline on Employee Performance - Winda Nurmayanti; Enang Narlan SAP (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Human resources have a major role in every organizational activity for the achievement of company goals. Employee performance levels need to be considered to achieve high productivity. Therefore this research was conducted wherein the pre-survey there were problems, especially in terms of motivation, work discipline, and employee performance, especially at Perum Jamkrindo Bandung Branch Office, and to determine the extent of the influence of motivation and work discipline on employee performance at Perum Jamkrindo Branch Offices Bandung. The method used in this research is the census method where this study takes the entire population of employees of the Jamkrindo Bandung Branch Office to become respondents. The data collected is using questionnaires and interviews. The questionnaire was distributed to 45 respondents and the data processing from the study used path analysis. The motivation variable can be stated in the good category and runs optimally. Likewise, work discipline variables are in a good category for employees as well, and employee performance variables are in a good category and have an effect on productivity at Perum Jamkrindo Bandung Branch Office. Motivation and Work Discipline have a significant relationship, employee motivation and performance have an influence, although not quite large, and work discipline on employee performance also has a greater influence.